THE EFFECTIVENESS OF SHARIA FINANCING MODEL IN BANK SYARIAH INDONESIA: LITERATURE REVIEW PERSPECTIVE - Aldiyansah; Destrian Isnaini; Dewi Rusmiati (I-Economics: A Research Journal on Islamic Economics)
This study aims to evaluate the effectiveness of the Islamic financing models implemented by Bank Syariah Indonesia (BSI) in supporting the development of micro, small, and medium enterprises (MSME). Islamic financing, using contracts such as mudharabah, musyarakah, and murabahah, is considered a fairer alternative to conventional financing systems. This research identifies several challenges in the implementation of Islamic financing, including the low level of Islamic financial literacy among the public and the need for strengthened regulations and government policies. Additionally, the study highlights the positive impact of partnerships between BSI and MSME, particularly those based in pesantren, in promoting local economic growth and enhancing financial inclusion. The conclusion emphasizes the importance of collaboration between the government, academia, and the Islamic banking industry to address existing challenges and improve the effectiveness of Islamic financing in Indonesia.